Business expansion feasibility study for UiTM Kampus Raub / Norlaila Abdullah - Abdullah, Norlaila (2008)
This business plan is prepared for UiTM Kampus Raub to layout the strategic framework of the campus, which currently offers certificate courses with 10 students despite of a decade of year's of existence. With this total of students' population, it has totally lost and forbade its competitiveness and market power in the area. The plan concentrates on the strategic elements of sustainability and competitiveness, since it is believed that understanding the prime factors related to the students' enrolment and courses to be offered will explicate the overall success of the campus alongside with the required allocation for subsidy.